2020
DOI: 10.29026/oea.2020.200003
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nonlinear optics for bio-imaging applications

Abstract: Nonlinear optics, which is a subject for studying the interaction between intense light and materials, has great impact on various research fields. Since many structures in biological tissues exhibit strong nonlinear optical effects, nonlinear optics has been widely applied in biomedical studies. Especially in the aspect of bio-imaging, nonlinear optical techniques can provide rapid, label-free and chemically specific imaging of biological samples, which enable the investigation of biological processes and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 227 publications
1
21
0
Order By: Relevance
“…It was observed that cysteine, serine, arginine, ascorbic acid, dopamine, H 2 O 2 , and various other metal ions Opto-Electronic Advances 113 .…”
Section: Photoluminescence-based Sensorsmentioning
confidence: 99%
“…It was observed that cysteine, serine, arginine, ascorbic acid, dopamine, H 2 O 2 , and various other metal ions Opto-Electronic Advances 113 .…”
Section: Photoluminescence-based Sensorsmentioning
confidence: 99%
“…In addition, CARS is derived from molecular vibration. Thus, it has chemical selectivity and chemical specificity [42]. Nonlinear optical techniques have been widely used to study biological samples because of their high optical spatial and temporal resolution, the absence of required additional labeling, nondestructive manipulation, and chemical specificity.…”
Section: Nonlinear Optical Microscopic Imagingmentioning
confidence: 99%
“…Nonlinear optical techniques have been widely used to study biological samples because of their high optical spatial and temporal resolution, the absence of required additional labeling, nondestructive manipulation, and chemical specificity. This part mainly introduces Aβ imaging by several nonlinear optical imaging techniques, including MPEF, SHG, THG, CARS, and SRS [42].…”
Section: Nonlinear Optical Microscopic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Femtosecond laser direct writing has emerged as a new technique for advanced micro- and nano-manufacturing, which can fabricate structures with ultrahigh precision and flexible morphologies , that have various applications. As an inherently 3D microfabrication technology, , femtosecond laser two-photon polymerization (TPP) has distinct advantages and has huge potential for the processing of innovative 3D micro- and nano-structures in biomedicine. With respect to the regulation of cell behavior, various types of biocompatible microstructures have been prepared via TPP microfabrication, such as freestanding proteinaceous spiral structures and polyhedral frameworks, nanogap plasmonic structures in microfluidic chips, 3D nanoporous architectures, nanostructured Brownian surfaces, and submicrometric patterned surfaces .…”
Section: Introductionmentioning
confidence: 99%